Knockdown of RLIM inhibits XIST expression and improves developmental competence of cloned male pig embryos. Issue 3 (1st March 2021) - Yang, Liusong; Wu, Xiao; Zhang, Ning; Shi, Junsong; Zhou, Rong; Su, Qiaoyun; Zheng, Enqin; Huang, Sixiu; Xu, Zheng; Hong, Linjun; Gu, Ting; Yang, Jie; et al.
Abstract: Ectopic expression of Xist on the putative active X chromosome is a primary cause of the low developmental efficiency of cloned mouse and pig embryos. Suppression of abnormal Xist expression via gene knockout or RNA interference (RNAi) can significantly enhance the developmental competence of cloned mouse and pig embryos. RLIM is a Xist expression activator, whereas REX1 is an Xist transcription inhibitor, as RLIM triggers Xist expression by mediating the proteasomal degradation of REX1 to induce imprinted and random X chromosome inactivation in mice. This study aimed to test whether the knockdown of RLIM and overexpression of REX1 can repress aberrant Xist expression and improve the developmental ability of cloned male pig embryos. Results showed that injection of anti‐RLIM small interfering RNA significantly decreased Xist messenger RNA abundance, increased REX1 protein level, and enhanced the preimplantation development of cloned male porcine embryos. These positive effects were not observed in cloned male pig embryos injected with REX1 expression plasmid, which might be due to the low expression efficiency of injected REX1 plasmid and/or the short half‐life of expressed REX1 protein. The findings from this study indicated that RLIM participated in the ectopic activation of Xist expression in cloned pig embryos by targeting REX1 degradation. Furthermore, this study provided a new method to improve cloned pig embryo development by the inhibition of Xist expression via RNAi of RLIM.